Chemotherapy Effect on Neutrophils Function in Leukemic Patients - Mashael A. Alkhanbashi,; Rasha A. Binmahfouz, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Neutrophils are chief phagocytic leukocytes, which form an essential part of the innate immune system that plays a key role in defense against living pathogens. Neutropenia has been considered to be the most important risk factor for severe infection during chemotherapy. In this study, the activity of neutrophils' function in adult leukemic patients before and after chemotherapy induction has been investigated. Whole blood samples were obtained from 32 leukemic patients with different cases, 8 patients from each: acute lymphatic leukemia, acute myeloid leukemia, chronic lymphatic leukemia and chronic myeloid leukemia. Immunophenotyping test was used to count T-lymphocytes, B-lymphocytes and Natural-killer lymphocytes. The mean results of the immunophenotyping test were in normal range so the count of these cells was not affected by chemotherapy. An oxidative burst test was used to quantify the neutrophils functions. There was significant differences between leukemia groups after chemotherapy (F = 3.923, p = 0.01). Acute lymphatic leukemia was the lower significant (p = 0.003) compared to the controls. There was no significant difference between the other cases and the controls. Acute lymphatic leukemia case was the most affected by chemotherapy.